THE GREAT KOBZAR AMONG TURKMENS (a view through the prism of earlier performed works) - Соегов, М. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article carries out research into little-known pages of contemporary Shevchenko studies. On the rich factual material (literary-fictional, cultural) the author exposes the problem of the reception of Taras Shevchenko’s creative work in Turkmenistan, outlines the Turkmen the matics of imagery in the Kobzar’s heritage, analyses Shevchenko’s works, translated into Turkmen, as well as supplies bright examples how Turkmen poets glorify the Ukrainian writer’s greatness and fame.